2016
DOI: 10.1111/jam.13157
|View full text |Cite
|
Sign up to set email alerts
|

Novel potential diagnostic test for Mycobacterium tuberculosis complex using combined immunomagnetic separation (IMS) and PCR-CTPP

Abstract: This study is the first report emphasizing the combination of IMS and PCR-CTPP for the detection of MTC and simultaneous identification of Myco. bovis from sputum. It could be used for TB diagnosis in resource-limited countries with high TB burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In this study, we developed a novel method using a combination of immunomagnetic beads separation and enrichment followed by RAA. Studies have reported that immunomagnetic separation technology is also used for the detection and enrichment of Listeria monocytogenes, Vibrio parahaemolyticus , Mycobacterium tuberculosis and Escherichia coli (Kraft et al 2017 ; Intorasoot et al 2016 ; Jiang et al 2020 ; Stewart et al 2017 ; Wadud et al 2010 ; Zeng et al 2014 ). These researchers used specific antibodies combined with magnetic beads to capture the target pathogen, which was then combined with PCR, LAMP and other techniques to perform nucleic acid amplification.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we developed a novel method using a combination of immunomagnetic beads separation and enrichment followed by RAA. Studies have reported that immunomagnetic separation technology is also used for the detection and enrichment of Listeria monocytogenes, Vibrio parahaemolyticus , Mycobacterium tuberculosis and Escherichia coli (Kraft et al 2017 ; Intorasoot et al 2016 ; Jiang et al 2020 ; Stewart et al 2017 ; Wadud et al 2010 ; Zeng et al 2014 ). These researchers used specific antibodies combined with magnetic beads to capture the target pathogen, which was then combined with PCR, LAMP and other techniques to perform nucleic acid amplification.…”
Section: Discussionmentioning
confidence: 99%
“…Ag85 complex proteins specifically interact with fibronectin [ 34 ] and exhibit robust sequence conservation across mycobacterium species, which may affect sensitivity and specificity of their detection by immunoassay methods. One recent study isolated mycobacteria from sputum samples using an Ag85B immunomagnetic enrichment approach prior to an Mtb -specific PCR analysis in an attempt to improve Mtb detection efficiency [ 35 ]. The sensitivity of this relatively labor-intensive approach for Mtb cases did not surpass Xpert-MTB/RIF assays results (89.9 vs. 95.2%), and this study did not examine the diagnostic sensitivity of this method for common NTM species causing pulmonary disease.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic-separation methods, already established as routine methods to detect Listeria monocytogenes (24), Salmonella spp. (25), and Escherichia coli O157:H7 (26) (27) in food and veterinary clinical samples, are promising alternatives to selectively separate and concentrate MTB (28)(29)(30)(31)(32) and MAP (33,34). Magnetic bead characteristics (composition, size, concentration, and surface modification) and the nature of coating ligands (antibodies, peptides, chemicals) are important factors enabling the concentration of the target bacteria and increasing the performance of further complementary detection methods such as culture, PCR, microscopy, antigen detection immunoassay, or phage assay (33,35,36).…”
Section: Introductionmentioning
confidence: 99%